Primary Insomnia: An Overview of Practical Management Using Cognitive Behavioral Techniques - Espie, C; Kyle, S (2009)
Primary insomnia is a prevalent disorder of sleep disturbance, impairing daytime functioning and health-related quality of life, leading to increased health care use. This article gives a brief overview of cognitive behavioral therapy as the treatment modality of choice for effectively ameliorating chronic sleep difficulties. Recommended and endorsed cognitive behavioral components are briefly described, and future research directions, focusing on improving the psychological management of insomnia, are outlined. Crown Copyright © 2009.